Abscisic acid mediated strawberry receptacle ripening involves the interplay of multiple phytohormone signaling networks - Li, Bai-Jun; Shi, Yan-Na; Jia, Hao-Ran; Yang, Xiao-Fang; Sun, Yun-Fan; Lu, Jiao; Giovannoni, James J.; Jiang, Gui-Hua; Rose, Jocelyn K. C.; Chen, Kun-Song (Frontiers in Plant Science, 2023)
As a canonical non-climacteric fruit, strawberry (Fragaria spp.) ripening is mainly mediated by abscisic acid (ABA), which involves multiple other phytohormone signalings. Many details of these complex associations are not well understood. We present an coexpression network, involving ABA and other phytohormone signalings, based on weighted gene coexpression network analysis of spatiotemporally resolved transcriptome data and phenotypic changes of strawberry receptacles during development and following various treatments. This coexpression network consists of 18,998 transcripts and includes transcripts related to phytohormone signaling pathways, MADS and NAC family transcription factors and biosynthetic pathways associated with fruit quality. Members of eight phytohormone signaling pathways are predicted to participate in ripening and fruit quality attributes mediated by ABA, of which 43 transcripts were screened to consist of the hub phytohormone signalings. In addition to using several genes reported from previous studies to verify the reliability and accuracy of this network, we explored the role of two hub signalings, small auxin up-regulated RNA 1 and 2 in receptacle ripening mediated by ABA, which are also predicted to contribute to fruit quality. These results and publicly accessible datasets provide a valuable resource to elucidate ripening and quality formation mediated by ABA and involves multiple other phytohormone signalings in strawberry receptacle and serve as a model for other non-climacteric fruits.